1984
DOI: 10.1021/ic00172a022
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and magnetic and EPR properties of bis(.mu.-azido)tetrakis(4-tert-butylpyridine)dicopper(II) perchlorate: a new copper(II) dinuclear complex with a large stabilization of the ground triplet state

Abstract: Wólfel (Technische Hochschule Darmstadt) provided access to the facilities (four-circle diffractometer and computer) of the Stoe + Cie. Application Laboratory, Darmstadt. The authors appreciate discussions on the manuscript with Dr. K. J. Wannowius. Propargylaldehyde was supplied by BASF, Ludwigshafen.Registry No. II, 22119-38-6; IV, 88106-41-6; Cu(TMBC)(C104)2, 88106-43-8; Cu(TMBC)I(C104), 88106-45-0; Cu(TMBC)(N3)(C104), 88106-47-2; Cu(TMBC)Br(C104), 88106-49-4; Cu(TMBC)(N03)2, 88106-51-8; Ni(TMBC)(C104)2, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(85 citation statements)
references
References 4 publications
4
80
0
1
Order By: Relevance
“…[1,2] In an effort to be concise, this work is restricted to the study of azido double-bridge copper(II) dinuclear systems. In these systems, the azido groups bridge the copper(II) ions either through one terminal nitrogen atom (m-1,1), in a socalled end-on coordination mode (abbreviated hereafter EO), [3][4][5][6][7][8][9][10][11][12][13][14][15][16] or through two terminal nitrogen atoms (m-1,3) in an end-to-end coordination mode (EE) as shown in Scheme 1. [11,[17][18][19][20][21][22][23] For both EO and EE systems, the bridge may be either symmetric (Scheme 1 a), when the two N À Cu bonds are Abstract: A new end-to-end azido double-bridged copper(II) complex [Cu 2 L 2 (N 3 ) 2 ] (1) was synthesized and characterized (L = 1,1,1-trifluoro-7-(dimethylamino)-4-methyl-5-aza-3-hepten-2-onato).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] In an effort to be concise, this work is restricted to the study of azido double-bridge copper(II) dinuclear systems. In these systems, the azido groups bridge the copper(II) ions either through one terminal nitrogen atom (m-1,1), in a socalled end-on coordination mode (abbreviated hereafter EO), [3][4][5][6][7][8][9][10][11][12][13][14][15][16] or through two terminal nitrogen atoms (m-1,3) in an end-to-end coordination mode (EE) as shown in Scheme 1. [11,[17][18][19][20][21][22][23] For both EO and EE systems, the bridge may be either symmetric (Scheme 1 a), when the two N À Cu bonds are Abstract: A new end-to-end azido double-bridged copper(II) complex [Cu 2 L 2 (N 3 ) 2 ] (1) was synthesized and characterized (L = 1,1,1-trifluoro-7-(dimethylamino)-4-methyl-5-aza-3-hepten-2-onato).…”
Section: Introductionmentioning
confidence: 99%
“…Some asymmetric EO systems [11][12][13] have now been found that exhibit antiferromagnetic Cu À Cu interactions, while several cases of ferromagnetic couplings have been reported for asymmetric EE systems. [11,22,23] In the early studies, [3][4][5][6][17][18][19][20] the symmetric EO coordination mode behavior seemed intrinsically ferromagnetic and independent of any structural parameters. This is why most previous theoretical studies focused on EO systems to explain such peculiar behavior, [24,[26][27][28][29][30] which was initially attributed to spin polarization effects.…”
mentioning
confidence: 99%
“…Pour tous les dimères symétriques di-µ-azido-cu(II) synthétisés jusqu'à présent, on observe soit un fort couplage ferromagnétique, soit un fort couplage antiferromagnétique, selon la manière dont les deux groupes azide pontent les cuivres, soit par une extrémité, 'end-on' (µ − 1, 1-), soit par les deux extrémités, 'end-to-end' (µ − 1, 3-). Jusqu'à récemment, une longue controverse a eu lieu sur l'origine du fort couplage ferromagnétique dans les dimères 'end-on' de composés di-µ-azide cu(II) [29]. Les deux mécanismes principaux invoqués sont :…”
Section: Chaînes Ferromagnétiques -Cu-nit-cu-unclassified
“…When the angle is smaller than 108°, it propagates ferromagnetic; otherwise, it is antiferromagnetic. [11][12][13][14][15] A more recent study based on theoretical calculations suggests a smaller critical angle (≈104°). [16][17][18] The second bridging mode (EE) usually gives rise to antiferromagnetic coupling and only in a few cases does ferromagnetic coupling occur through this pathway.…”
Section: Introductionmentioning
confidence: 99%